Eighteenth-Century British Premiers - Leonard, D. author. aut Link
VII, 256 p.
Keywords: Following his earlier surveys of 19th and 20th Century British Prime Ministers, Dick Leonard turns his attention to their 18th Century predecessors, including such major figures as Robert Walpole, the Elder Pitt (Lord Chatham), Lord North and the Younger Pitt.